Analisis Status Kewarganegaraan WNI Eks ISIS Berdasarkan Undang-Undang Kewarganegaraan - Satun, Sofan; Purwati, Indira (Lembaga Publikasi Ilmiah Nusantara, 2024)
This study analyzes the citizenship status of Indonesian citizens (WNI) who were former members of ISIS based on the provisions in the Indonesian Citizenship Law. The main focus of the study is to identify whether joining a group designated as an international terrorist organization can result in the loss of citizenship under Article 23 of Law No. 12 of 2006. The analysis considers various factors, including evidence of voluntary actions in joining foreign organizations and the legal implications arising from international recognition of ISIS as a global threat. The study also addresses legal and ethical dilemmas in managing the citizenship status of individuals potentially posing a threat to national security, while providing policy recommendations grounded in law and human rights principles. The findings indicate a strong legal basis for revoking citizenship; however, its implementation requires caution to align with principles of justice and the constitution.